Image(s) a informacja - Strzelecki, Jarosław (Wydawnictwo Naukowe UAM, 2014)
This article presents philosophical reflections on information. Bergson’s metaphysical category of image(s) is juxtaposed with the concept of information. This combination leads to the conclusion that any system (animate or inanimate one) remains “informationally” related to its environment in a metaphysical way.
Image(s) and Information
Keywords: information; image; metaphysics; nature